SCHOOL-FAMILY COLLABORATION TOWARDS VIOLENCE PREVENTION IN SCHOOL PUPILS - Sylaj, Vlora (European Scientific Journal, ESJ, 2014)
This article aims to contribute to the growing interest andconsideration to prevention the student violence by the school and thefamily. This actually leads to the optimization of the role of the school.Through answering the research questions, the paper could serve readers toreflect for the better cooperation between parents and school in terms ofprevention the student violence by the school and the family.This study reflects upon the importance of qualitative collaboration,namely to enrich the public opinion with the valuable information about thecooperation between school and home. The purpose of this article is toascertain whether it affects the level of contacts between school and familyby supporting the success of students from the school. This study usedquantitative method and aims to find answers to the following questions:What are the school and the family factors that support the success ofstudents? Does this affect the level of contacts between the family and theschool?Research hypothesis: The level of contacts between the school andfamilies affected by the support by the school for students‘ success. We haveincluded 400 teachers and 400 parents from rural areas in this study, as wellas 300 teachers and 300 parents of fourth classes‘ from the urban areas. Theycome from the various city schools in Kosovo. Systematic sample wasrandomly selected, and we have compiled the questionnaire. A team ofpedagogues, who have been previously trained to use this questionnaire, tookattitudes of both subjects. Data were analyzed by SPSS 20 program. Thestudy has reached some findings and conclusions. Participants’ responsesindicate that the level of contact between the school and families is affectedby the factor to prevention the student violence by the school and the family.